Impelementation of Flood Disaster Control Regulations with a Multisectoral Approach - Adi, Emmanuel Ariananto Waluyo; Ashari, Bayu; Simanullang, Sintong Martunas M; Muhammad, Raihan Bari (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
of land administration, public works and water resources, transmigration, environment and peatland management, energy, public financing, legal governance, and inter-institutional coordination. A normative juridical framework, enriched with institutional process mapping, was employed to assess how cross-sectoral policies have shaped hydrological vulnerability and influenced the effectiveness of flood-mitigation efforts. The analysis indicates that the effectiveness of licensing regimes, spatial planning, and field-level monitoring has been constrained by tenure uncertainty, inconsistencies in spatial datasets, weak geospatial verification, and deficits in upstream infrastructure maintenance. Granular violations including land clearing, peat canalization, and incomplete mine reclamation were also found to remain insufficiently addressed by conventional enforcement mechanisms, as reflected in numerous field findings circulating in the public domain. From the land-administration perspective, tenure certainty and risk-layer consolidation are required to be strengthened; from the water-resources perspective, synchronization of planning and infrastructure maintenance must be ensured; from the transmigration perspective, population placement is mandated to be based on hazard mapping and rights protections; from the environmental and peatland perspective, ecological restoration and rewetting are viewed as essential prerequisites; from the energy sector, logistical preparedness and mitigation-budget protection are required to be enhanced; and from the legal perspective, regulatory harmonization and tiered sanctions are required to ensure effective ecological recovery. At the institutional level, strengthened coordination across ministries is deemed necessary to enable consistent implementation of these recommendations. Accordingly, it is concluded that flood management in Sumatra can only be achieved through an integrated and binding governance framework grounded in a unified risk map, systematic licence auditing, and measurable ecological rehabilitation.